Extraction of pectin from some local fruits and its use in jam processing - Abdelwahab, Azhari; Sulieman, Abdel Moneim; El-Hardallou, Sirelkhatim (Gezira Journal of Agricultural Science, 2011)
In the present study, pectin was extracted from orange, grapefruit and guava fruits and used in jam processing. The percentages of pectin extracted from orange, grapefruit and guava powder were 28%, 26.4% and 2.8%, respectively. Jam made using pectin extracted from grapefruit (GrPJ), orange (OPJ) and guava (GuPJ) contained 66%, 67% and 67% total soluble solids, respectively. The reducing sugar contents of GrPJ, OPJ and GuPJ were 4.7%, 5%, and 4.1%, respectively, while the total sugar contents were 8.7%, 8.5% and 8.4%, respectively. The pH values of GrPJ, OPJ and GuPJ were 3.5, 3.4 and 3.6, respectively. Moisture contents of GrPJ, OPJ and GuPJ were 53.7%, 45.8% and 47.4%, respectively, and the ash contents were 0.23%, 0.18%, and 0.21%, respectively.  The contents of sodium were 36, 34 and 35 mg/100g in OPJ, GrPJ and GuPJ, respectively, while the contents of potassium were 60, 68 and 69 mg/100 g, respectively. The contents of calcium were 80, 79 and 78 mg/100 g, respectively. The content of vitamin C of OPJ, GrPJ and GuPJ were 0.01, 0.02, and 0.02 mg/100g, respectively. Microbial analysis revealed that all jam samples were devoid of coliforms, staphylococci , yeasts and moulds. The sensory analysis indicated that all types of jams were accepted by panelists who preferred them in the order of jam made using commercial pectin followed by jam made using pectin extracted from orange, grapefruit and guava. Most panelists preferred the jam made using commercial pectin due to its appealing color and appearance.    تم في هذه الدراسة إستخلاص البكتين من بعض الفواكه المحلية  (القريب فروت , البرتقال والجوافة) وأستخدم في تصنيع مربى بإستعمال القرع كمادة خام. وقد وجدت النسبة المئوية للبكتين المستخلص من مسحوق البرتقال تساوي 28 ٪ ، ومن مسحوق القريب فروت تساوي 26.4 ٪ والنسبة المئوية للبكتين المستخلص من  الجوافة يساوي 2.8 ٪. إحتوت المربى المصنعّة باستخدام البكتين المستخلص من القريب فروت ((GrPJ،البرتقال OPJ)) والجوافة (GuPJ) على 66٪ ، 67 ٪ و 67٪ من المواد الصلبة الذائبة الكلية ، على التوالي. كانت نسبة السكر المختزل لـGrPJ ، OPJ وGuPJ 4.7 ٪ ، 5 ٪ ، و 4.1 ٪ على التوالي، في حين بلغ إجمالي السكر 8.7 ٪ ، 8.5 ٪ و 8.4% على التوالي. كانت قيم الأس الهيدروجينى لـGrPJ ، OPJ وGuPJ 3.5 ، 3.4 و 3.6 على التوالي. كان محتوى الرطوبة لـ GrPJ ، OPJ وGuPJ كان 53.7 ٪ ، 45.8 ٪ و 47.4 ٪ على التوالي ، وكان محتوى الرماد 0.23 ٪ و 0.18 ٪ و 0.21 ٪ على التوالي. محتوى الصوديوم هو 36 , 34 و 35 (ملجم/100جم) في OPJ ، GrPJ وGuPJ ، على التوالي ، في حين أن محتوى البوتاسيوم كان 60 , 68 و 69 ) ملجم/100جم) علي التوالي, ومحتوى الكالسيوم كان 80 و 79 و 78 (ملجم/100جم)  على التوالي. محتوى فيتامين "ج" منOPJ ، GrPJ وGuPJ كان 0.01 ،  0.02 ، 0.02 (ملجم/100جم) ، على التوالي. أشار التحليل الميكروبي إلى أن جميع عينات المربي كانت خالية من البكتريا القولونية, البكتريا العنقودية, ومن خلايا الأعفان والخمائر. التحليل الحسي أشار إلى أن جميع أنواع المربى وجدت قبولاً من المحكمين بدرجة كبيرة خصوصاً  بالنسبة للمربى المصنعة باستخدام البكتين التجاري بالمقارنة مع مربي البكتين المستخلص من البرتقال, القريب فروت والجوافة  على التوالي. فضّل معظم المحكمين مربي البكتين التجاري حسب اللون والمظهر الجذاب.